2022
DOI: 10.3390/healthcare10010105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice among Physical Therapists toward COVID-19 in the Kingdom of Saudi Arabia—A Cross-Sectional Study

Abstract: To curb the COVID-19 pandemic, the knowledge, attitude, and practice (KAP) of preventive measures play an essential role, and healthcare workers have had to endure a burden to care for COVID-19 patients. Thus, this study aimed to assess the weight of the KAP of physiotherapists in Saudi Arabia during the COVID-19 pandemic. This was a cross-sectional study, where we circulated an online KAP questionnaire to 1179 physical therapists, and among those, 287 participated and completed the questionnaire. The collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…In terms of attitude, more than 80% of the staff of China-Guinea Friendship Hospital had a positive attitude. This result is higher than those of previous studies among medical staff (those participants had a moderate or positive attitude rate of 50.5–72.2%) ( 10 , 22 24 ), and the reason may be related to the higher rate of knowledge correctness ( 17 , 23 , 25 ). Almost 65.03% of hospital staff believed that COVID-19 would eventually be overcome in our study, which is similar to the results of some previous studies ( 10 ).…”
Section: Discussioncontrasting
confidence: 75%
“…In terms of attitude, more than 80% of the staff of China-Guinea Friendship Hospital had a positive attitude. This result is higher than those of previous studies among medical staff (those participants had a moderate or positive attitude rate of 50.5–72.2%) ( 10 , 22 24 ), and the reason may be related to the higher rate of knowledge correctness ( 17 , 23 , 25 ). Almost 65.03% of hospital staff believed that COVID-19 would eventually be overcome in our study, which is similar to the results of some previous studies ( 10 ).…”
Section: Discussioncontrasting
confidence: 75%
“… 504 participants Online questionnaire Knowledge and practice gaps among the population, especially in the young age group, had to be covered by the execution of training programs through workshops or include courses in the curriculum of MOH. Alshahrani/Jan 2022 118 Knowledge, Attitude, and Practice among Physical Therapists toward COVID-19 in the Kingdom of Saudi Arabia-A Cross-Sectional Study 287/1179 physical therapists Online questionnaire Physical therapists in Saudi Arabia exhibit good knowledge, attitude, and practice toward COVID-19. Moussa/Jan 2022 119 Association of Fear of COVID-19 and Health Literacy Among the General Public in Saudi Arabia: A Cross-Sectional Assessment.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…A review of the relevant literature indicated concerns amongst the educators and coaches about the effective methods to produce and possess solid knowledge about the related physical therapy knowledge with an appreciation for the importance of treatment methods [21]. In Saudi Arabia, a variety of debates have been addressed on the manner, which issue of knowledge about the physical therapy among the sports practitioners for best and professional physical therapy practices [22]. The perceptions were ranged from having findings critique of the studies to launching new research proposals with actual performing research projects to adopt and assist the scholars and research project to actual complete future independent research projects [23].…”
Section: Literature Reviewmentioning
confidence: 99%